Chapter 9. Preparing for the Long Term - Brzustowski, Tom (Les Presses de l’Université d’Ottawa | University of Ottawa Press, 2008)
Qualitative change is the acid test of leadership.This final chapter deals with preparing to achieve higher productivity and a greater prosperity for Canada, and to sustain it over the long term. More change is required, and much of it will be qualitative change. It will not be enough to do a little more of this and a little less of that, improve some things, and abandon a few others. We will have to do some important things very differently, and some new things that we’ve never done before and...